A New Perspective for Fiscal Federalism: The NK Model. Issue 4 (1st October 2016) - Faggini, Marisa; Parziale, Anna
Abstract: Economic models of fiscal federalism, according to different settings, are generally linear and static, offering unique and deterministic solutions starting with simplifying assumptions. This article stems from the idea of investigating how decision-makers, abandoning their traditional economic models and focusing on innovative components of evolutionary economics instead, can achieve better performance results in organizing and optimizing an economic system based on fiscal federalism. For this purpose, fiscal federalism must be understood as a dense network of economic relationships between different complex adaptive and co-evolving systems, the jurisdictions, linked by strong interdependencies. A better understanding of the links between interdependence will be provided by Stuart Kauffman's NK model. The relevance of the NK model in the study of economic organizations has been noted in the relevant literature. This literature, however, neglects the problem of co-evolution, which underpins our article.